The Combination Therapy of Dissolution Using Carbonated Liquid and Endoscopic Procedure for Bezoars: Pragmatical and Clinical Review - Kohei Ogawa; Kenya Kamimura; Ken-ichi Mizuno; Yoko Shinagawa; Yuji Kobayashi; Hiroyuki Abe; Yukari Watanabe; Shunsaku Takahashi; Kazunao Hayashi; Junji Yokoyama; Manabu Takeuchi; Masaaki Kobayashi; et al. (Gastroenterology Research and Practice)
Bezoars are relatively rare foreign bodies of gastrointestinal tract and often cause ileus and ulcerative lesions in the stomach and subsequent bleeding and perforation due to their size and stiffness. Therefore, the removal of bezoars is essential and recent development of devices, the endoscopic removal procedure, is often applied. However, due to their stiffness, simple endoscopic removal failed in not a few cases, and surgical removal has also been used. Recently, the efficacy of a combination therapy of endoscopic procedure and dissolution using carbonated liquid has been reported. To develop the safe and effective removal procedure, we carefully reviewed a total of 55 reported cases in this study including our 3 additional cases, successfully treated with dissolution with endoscopic fragmentation. In summary, the data showed the efficiency in the combination therapy, treating the larger size of bezoar and reducing the length of hospital stay. To the best of our knowledge, this is the largest pragmatical and clinical review for the combination therapy of dissolution and endoscopic treatment for bezoars. This review should help physicians to manage bezoars more efficiently.